2021
DOI: 10.1177/08919887211018267
|View full text |Cite
|
Sign up to set email alerts
|

Mood Disorders and Anxiety in Parkinson’s Disease: Current Concepts

Abstract: Mood disorders and anxiety significantly impact the prognosis and disease course of Parkinson’s disease. Non-motor symptoms of Parkinson’s disease such as apathy, anhedonia, and fatigue overlap with diagnostic criteria for anxiety and depression, thus making accurate diagnosis of mood disorders in Parkinson’s disease patients difficult. Furthermore, treatment options for mood disorders can produce motor complications leading to poor adherence and impaired quality of life in Parkinson’s disease patients. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 94 publications
0
14
0
Order By: Relevance
“…Motor symptoms often interact with non-motor symptoms, like anxiety, in a bidirectional manner 45. The emergence of anxiety can intensify motor symptoms, potentially leading to the onset of motor complications in patients with PD 46. Given this complex relationship, a more holistic approach that considers both motor symptoms and associated mental health aspects is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Motor symptoms often interact with non-motor symptoms, like anxiety, in a bidirectional manner 45. The emergence of anxiety can intensify motor symptoms, potentially leading to the onset of motor complications in patients with PD 46. Given this complex relationship, a more holistic approach that considers both motor symptoms and associated mental health aspects is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…9,30 Our study found approximately 74% of patients with diagnosed anxiety had at least one form of documented treatment, most commonly pharmacotherapy. Of note, treatment guidelines for anxiety in PD continue to rely on observational study and expert opinion, 11 which informed the choice of pharmacotherapies included to describe current practice patterns. To our knowledge, CBT is the only therapy demonstrated to be effective in patients with PD and comorbid anxiety by randomized controlled trial.…”
Section: Discussionmentioning
confidence: 99%
“…9 While cognitive generally follows that of the general population, with SSRIs and psychotherapy considered to be first-behavioral therapy (CBT) has been demonstrated to be effective for anxiety in PD, 10 no other controlled trials for anxiety treatment have been conducted thus far in people with PD. 11,12 Psychotherapy, pharmacotherapy, and a combination have all been shown to be more effective than placebo in the treatment of anxiety disorders. 13,14 Pharmacotherapy - in particular selective serotonin reuptake inhibitors (SSRIs), tricyclic antidepressants (TCAs), and benzodiazepines- is useful in the management of anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, fatigue is reported by approximately half of the patients with PD 36,35,37 and is associated with an increased α-synuclein oligomer level in the cerebrospinal fluid 38 . Lintel et al 39 argue that symptoms of fatigue overlap with the diagnostic criteria for depression and hence challenging to separate. This thinking aligns with our results that identify these two symptoms as the most significant factors associated with poorer hrQoL in patients with iRBD.…”
Section: Discussionmentioning
confidence: 99%